THE DYNAMICS OF THE POPULATIONS OF SOME WEEDS IN THE AGROPHYTOCENOSES OF SPRING WHEAT - Соколовська, І. М. (Scientific Progress & Innovations, 2014)
The study of the current state of weed populations in agrocenoses is important for predicting their subsequent development and effect on yield, quality and productivity of crops. At the beginning of the formation of the agrophytocenoses of spring wheat the largest groups of the weedy component were the populations of young weeds. They did not compete with the cultivated plants, finished their life cycle before, so did not have a significant effect on the formation of the yield of the main crop. The populations of the root-and-shoot perennial weeds (Cirsium arvense. Cirsium arvense. Convolvulus arvensis L.. ) in this period formed the least numerical segetal large group of plants. But they differed of high ecological stability, performances of vitality and high ability to compete with cultivated plants, that’s why they inflicted the most damage to crops of spring wheat. The populations of this group of plants acquired the environmental stability and had a significant influence on the formation of the agrophytocenoses and yield of spring wheat without conduction proper and timely measures.